PERILAKU KONSUMEN AGROWISATA DI KAMPUS UPN“VETERAN” JAWA TIMUR - Parsudi, Setyo; Santoso, Juli (Berkala Ilmiah AGRIDEVINA, 2017)
The Agriculture Faculty of the East Java “Veteran” National Development University shall develop the agrotour in the campus area which can be utilized by students and thesurroundings community as the health, pleasant and useful recreation place for itsvisitors. In order that the development of the agrotour meet with the concumersexpectation, it is needed a good planning, in which one of them should consider theresponses and behaviors of the agrotour consumers or consumers to be. The purposes ofthis research are: 1) To study the responses of consumers to the agrotour development, 2)To study the aim of consumers to visit to agrotour, and 3) To study the behavior ofagrotour consumers in the East Java “Veteran” National Deelopment University campus.The result of research found that the largely consumers/consumers to be of the East Java“Veteran” National Deelopment University agrotour agreed or very agreed with thedeveloped the agrotour. The aim of consumers to visit is, prima facie, to relax whileincreasing knowledge. Whereas, the behaviors of agrotour consumers are: 1) Thefrequence to visit mostly once a week, 2) The visiting time mostly at noon and afternoon,3) The trasnportations the consumers utilize mostly motorcycles, 4) The consumersmostly come together with friends or families. The expectations of consumers to theexisting agrotour are, largely, that it is able to be a recreation place and city lungs, to bea medium of environmental conservation and science development and to be a medium ofentrepreneurship development.